Estudo de técnicas para a melhoria da relação entre densidade de potência e rendimento de conversores CA-CC com estágio integrado de potência aplicáveis a carregamento on-board de veículos elétricos - Barbosa, Samanta Gadelha (2025)
This thesis proposes new techniques to improve power density and efficiency in single-stage single-phase AC-DC converters with high-frequency isolation, aiming at applications in on-board chargers for electric vehicles. The main contributions include: (i) the development of new modulation techniques applied to single-phase interleaved AC-DC converters with three (3LI) and four legs (4LI); and (ii) the design of a novel integrated magnetic arrangement. In the first part, modulation variants are introduced to extend the Zero Voltage Switching (ZVS) operation over the AC grid cycle, enabling higher switching frequencies with reduced switching losses. On the other hand, increased implementation complexity, higher circulating currents, and a greater number of magnetic components are observed. Theoretical analyses are validated through simulations and experimental tests. Assuming suitable semiconductor devices, the proposed modulations result in lower losses for switching frequencies above 160 kHz in the 3LI and 75 kHz in the 4LI. For the 4LI, enhanced power density is also observed for magnetic volumes below 500 cm3. In the second part, a cubic magnetic arrangement is developed, integrating the AC filter inductor, two autotransformers, and two transformers from the 4LI topology, with the possibility of using leakage inductances for energy transfer. Based on a simplified design methodology, an iterative process is employed to achieve optimized configurations without relying on finite element tools. The proposed arrangement is validated by simulations and tests with a 6.6 kW prototype, demonstrating superior efficiency even under variable load conditions. Additional advantages include the use of standard core geometries and ferrite as the sole magnetic material. A theoretical analysis based on the Pareto front shows that, for switching frequencies between 50 kHz and 200 kHz, the integrated magnetic allows reductions of up to 16.1% in losses and 51.2% in magnetic volume compared to the conventional approach. The work also discusses identified limitations and suggests directions for future research. Overall, the proposed strategies proved promising for applications requiring high efficiency and compactness, such as onboard chargers for electric vehicles.